A non-yellowing dry surface resin and preparation method thereof
By using raw materials such as polycarbonate diol, polyether diol, aliphatic isocyanate and diamine, combined with antioxidants and light stabilizers, and adding sericite powder and microcrystalline cellulose as fillers, a non-yellow-deformed dry surface resin was prepared, which solved the problem of the dry surface resin being prone to yellowing and significantly improved its light stability and mechanical properties.
Patent Information
- Application Number
- CN202211446109.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-18
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2042-11-18
AI Technical Summary
Common dry surface resins are prone to yellowing, which affects the aesthetics and performance of synthetic leather.
Polycarbonate diol, polyether diol, aliphatic isocyanate, diamine, etc. are used as raw materials, combined with antioxidants and light stabilizers to prepare a dry surface resin without benzene ring, and sericite powder and microcrystalline cellulose are added to the resin to improve mechanical properties and light stability.
It significantly improves the light stability and yellowing resistance of the dry surface resin, enhances its mechanical properties, wear resistance and high temperature resistance, and extends the service life of the synthetic leather.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the field of polyurethane resins, and more specifically, to a non-yellowing dry surface resin and a preparation method thereof. Background Art
[0002] Dry surface resin is often used in the field of synthetic leather. After the synthetic leather is veneered with dry surface resin and then processed by a vacuum grain absorption machine, it will have clear texture and full feel. The appearance, practicality and comfort of the synthetic leather are all affected by the dry surface resin.
[0003] Common dry surface resins use isocyanates and polyol compounds as raw materials, react under the action of chain extenders, catalysts and other additives, and finally add terminators to obtain dry surface resins. Aromatic isocyanates, such as toluene diisocyanate or diphenylmethane diisocyanate, are generally used as raw materials in preparation. Aromatic isocyanates contain benzene rings in their molecular structure, which makes the obtained dry surface resin have good mechanical strength.
[0004] However, common dry surface resins are prone to yellowing. The main reason is that the benzene ring structure of aromatic isocyanate will undergo photooxidation under ultraviolet light, resulting in electron transition, making the resin yellow. At the same time, after the dry surface resin absorbs water, some polyurethane bonds in the resin are hydrolyzed to form carboxylic acid and amide. Under the action of photooxidation, the amide bond and carboxylic acid bond break, which will also cause the resin to yellow, affecting the aesthetics of the synthetic leather. In view of this, the inventor believes that it is necessary to develop a dry surface resin that does not yellow and has better performance. Summary of the invention
[0005] In order to obtain a non-yellowing dry-process surface layer resin with excellent performance, the present application provides a non-yellowing dry-process surface layer resin and a preparation method thereof.
[0006] In the first aspect, the present application provides a non-yellowing dry-process surface resin, which adopts the following technical solution:
[0007] A non-yellowing dry-process surface resin comprises the following components in parts by weight:
[0008] 155-165 parts of polycarbonate diol,
[0009] 9-17 parts of polyether diol,
[0010] Aliphatic isocyanate 50-60 parts,
[0011] 20-30 parts of diamine,
[0012] Antioxidant 0.2-0.8 parts,
[0013] Light stabilizer 2-5 parts,
[0014] Chain extender 0.5-1 part,
[0015] Catalyst 0.02-0.1 parts,
[0016] Terminator 0.3-0.5 parts,
[0017] 3-5 parts of leveling agent,
[0018] 685-785 parts of solvent,
[0019] Filler 0-15 parts,
[0020] Defoaming agent 0-0.1 parts.
[0021] By adopting the above technical scheme, a certain mass fraction of polycarbonate diol polyether diol is used as a polyol raw material, so that the dry surface resin has excellent wear resistance; aliphatic isocyanate is introduced as a raw material, because there is no benzene ring in the molecular structure of aliphatic isocyanate, the yellowing phenomenon caused by isocyanate being oxidized to a color-developing group by light is reduced; the use of diamine compounds as raw materials can give the resin excellent light stability; aliphatic isocyanate, polyol, diamine, and chain extender constitute the hard segment of the dry surface resin, so that the hard segment contains strong polar groups such as carbamate group and urea group, giving the dry surface resin better heat resistance. Antioxidants can capture oxygen free radicals and reduce the occurrence of photooxidation reactions. Light stabilizers can improve the light stability of dry surface resins. The combination of antioxidants and light stabilizers can effectively inhibit the yellowing of dry surface resins under the action of ultraviolet rays. Adding a certain mass fraction of fillers to the dry surface resin can improve the mechanical properties of the resin without destroying the properties of the resin itself, and make up for the defects of the dry surface resin in rigidity, temperature resistance, wear resistance, etc. caused by the fact that aliphatic isocyanates do not contain a benzene ring structure. Using the above-mentioned mass fractions of each component as a raw material can produce a non-yellowing dry surface resin with excellent performance.
[0022] Preferably, the aliphatic isocyanate is selected from one or a combination of 4,4'-dicyclohexylmethane diisocyanate and isophorone diisocyanate.
[0023] By adopting the above technical solution and the above aliphatic isocyanate, the prepared resin has excellent light stability, weather resistance, drug resistance and mechanical properties.
[0024] Preferably, the diamine is isophoronediamine.
[0025] By adopting the above technical solution, the prepared resin has excellent light stability and drug resistance.
[0026] Preferably, the chain extender is selected from one or a combination of ethylene glycol, propylene glycol or 1,4-butanediol.
[0027] By adopting the above technical solution, using the above small molecule diol as a chain extender can reduce the occurrence of branching reactions, and at the same time, hydrogen bonds are easily formed between chain segments during the reaction process, thereby improving the tensile strength, hardness and toughness of the dry surface layer resin.
[0028] Preferably, the polyether diol is polytetrahydrofuran diol.
[0029] By adopting the above technical scheme, the dry surface resin can have better low temperature resistance and hydrolysis resistance.
[0030] Preferably, the filler is selected from one or a combination of ultrafine transparent powder, sericite powder, muscovite powder, barium sulfate powder, and microcrystalline cellulose.
[0031] By adopting the above technical solution, the mechanical properties, wear resistance, high temperature resistance and aging resistance of the resin can be improved. The above filler is transparent or white, which reduces the influence of the filler on the color of the finished dry surface resin product.
[0032] Preferably, the filler comprises sericite powder and microcrystalline cellulose in a mass ratio of 6-8:1.
[0033] By adopting the above technical scheme, the sericite powder is flaky and has excellent dispersibility and suspension, and can be arranged in parallel flaky layers in the dry surface resin, effectively reducing the penetration of water and the hydrolysis of the polyurethane molecules of the dry surface resin, while giving the dry surface resin excellent glossiness and improving the glossiness of the texture formed after veneer. In addition, the sericite powder has excellent ultraviolet and infrared shielding performance, and can effectively improve the anti-ultraviolet performance of the dry surface resin, reduce the occurrence of photooxidation reaction, and improve the aging resistance and light stability of the dry surface resin. The microcrystalline cellulose has a porous structure and has good hygroscopicity and adsorption. There is a strong hydrogen bond between the microcrystalline cellulose molecules. When moisture in the air penetrates into the dry surface resin, the microcrystalline cellulose can effectively absorb water molecules, thereby reducing the possibility of the polyurethane molecules of the dry surface resin being hydrolyzed.
[0034] Sericite powder forms parallel and dense sericite layers in the dry surface resin, and microcrystalline cellulose is distributed between the sericite layers. The sericite layer close to the surface can shield ultraviolet rays and block the penetration of some water molecules. When water molecules pass through the sericite layer, they will be adsorbed by the microcrystalline cellulose distributed between the layers, further reducing the penetration of water and the possibility of polyurethane molecules being hydrolyzed. At the same time, the inner sericite layer continues to play a role in blocking water. The sericite powder and microcrystalline cellulose work together to effectively reduce the possibility of polyurethane molecules being hydrolyzed and photo-oxidized and causing yellowing.
[0035] The strong adsorption capacity of microcrystalline cellulose enables it to effectively adsorb and combine with the resin molecules of the dry surface resin, so that the microcrystalline cellulose is stably distributed between the sericite layers, thereby enhancing the stability of the sericite layer, and further improving the stability of the dry surface resin on the surface of synthetic leather.
[0036] Preferably, the filler is a surface-treated filler, and the specific operation is as follows:
[0037] s1. Bake the filler at 100-130°C for 2-4h, and stir and mix at 65-70°C and 500-700r / min; s2. Melt the aluminate coupling agent at 70-75°C;
[0038] s3: Mix the mixed filler with a mass ratio of 100:1-3 and the melted aluminate coupling agent at 80°C-90°C, stir at a speed of 300-500 r / min for 20-30 minutes, and then cool at room temperature to obtain surface-treated filler particles.
[0039] By adopting the above technical solution, the aluminate coupling agent enables the filler to have excellent dispersibility in the organic resin, while being able to improve the mechanical properties of the filler and reduce the water absorption of the dry surface layer resin.
[0040] Preferably, the antioxidant comprises a hindered phenol antioxidant and a phosphite antioxidant in a mass ratio of 1:1-3.
[0041] By adopting the above technical scheme, there are active H atoms in the hindered phenol antioxidant molecules, and the H atoms can be separated from the molecules and combined with peroxy free radicals to form hydroperoxides, effectively capturing peroxy free radicals and terminating the oxidation process; the phosphite antioxidants can delay the generation of free radicals and decompose hydroperoxides to form stable inactive compounds, that is, the hindered phenol antioxidants and the phosphite antioxidants produce a positive synergistic effect, which effectively delays the occurrence of photooxidation reactions and enhances the yellowing resistance of the dry surface resin.
[0042] Preferably, the solvent comprises 135-185 parts of isopropanol and 550-600 parts of N,N-dimethylformamide per part by weight.
[0043] By adopting the above technical solution, the mixed solvent can effectively dissolve each component and provide conditions for the reaction to occur.
[0044] In a second aspect, the present application provides a method for preparing a non-yellowing dry-process surface layer resin, using the following technical solution:
[0045] A method for preparing a non-yellowing dry surface resin comprises the following steps:
[0046] Step 1: According to the proportion, polycarbonate diol, polyether diol, aliphatic isocyanate, chain extender, antioxidant, light stabilizer and catalyst are mixed, 65-150 parts by weight of solvent are added, and the mixture is reacted at 90° C.-100° C. for 2-3 hours to prepare a prepolymer;
[0047] Step 2: adding 340-500 parts by weight of solvent to the prepolymer, cooling to 50°C-55°C, adding diamine, and mixing to obtain a reaction solution;
[0048] Step 3: Add the remaining solvent, terminator and leveling agent to the reaction solution, mix well to obtain a non-yellowing dry surface resin.
[0049] Preferably, the viscosity of the dry surface layer resin is 30-60 Pa.S / 25°C.
[0050] By adopting the above technical solution, the reaction stability and the yellowing resistance of the dry surface resin are improved.
[0051] Preferably, the method for preparing the non-yellowing dry surface resin further comprises:
[0052] Step 4: Take 40%-60% dry surface resin by mass, add filler thereto, stir at 40℃-50℃ at a speed of 200-300r / min for 3-4h; then add the remaining dry surface resin and defoamer, continue stirring for 1-2h, and obtain non-yellowing dry surface resin after cooling.
[0053] By adopting the above technical solution, a non-yellowing dry surface resin with better mechanical properties such as wear resistance can be produced.
[0054] In summary, this application has the following beneficial effects:
[0055] 1. Since the present application uses polycarbonate diol, polyether diol, aliphatic isocyanate, diamine, etc. as raw materials for the dry surface resin, the yellowing resistance of the dry surface resin is enhanced, and antioxidants and light stabilizers are used in combination to further enhance the light stability and yellowing resistance of the resin; in addition, adding a certain mass fraction of fillers can improve the mechanical properties, wear resistance and high temperature resistance of the resin without destroying the properties of the resin itself;
[0056] 2. In the present application, sericite powder and microcrystalline cellulose are preferably used as fillers. The combination of sericite powder and microcrystalline cellulose can effectively reduce the possibility of hydrolysis of polyurethane molecules in the dry surface resin. The sericite powder has excellent UV resistance, which further enhances the light stability of the dry surface resin.
[0057] 3. The method of the present application improves the stability of the reaction and the yellowing resistance of the dry surface resin by first preparing the prepolymer and then adding diamine to increase the viscosity, so as to obtain a non-yellowing dry surface resin with excellent performance. DETAILED DESCRIPTION
[0058] The present application is further described in detail below with reference to the embodiments.
[0059] Preparation example of filler
[0060] Preparation Example 1
[0061] The surface treatment steps of the filler are as follows:
[0062] s1 85.7 g of sericite powder and 14.3 g of microcrystalline cellulose were baked at 110 °C for 2 h and stirred at 65 °C and 600 r / min for 15 min;
[0063] s2 melt 10g of aluminate coupling agent at 75℃;
[0064] s3: Add the baked filler and the melted aluminate coupling agent into a high temperature stirrer, stir at 80°C and 500 r / min for 30 minutes, and then cool at room temperature to obtain a surface-treated filler.
[0065] In this preparation example, the model of the aluminate coupling agent is DL-411, the particle size of the sericite powder is 1250 mesh, and the model of the microcrystalline fiber powder is M105.
[0066] Preparation Example 2
[0067] The only difference between this preparation example and preparation example 1 is that the amount of aluminate coupling agent is 20 g.
[0068] Preparation Example 3
[0069] The only difference between this preparation example and preparation example 1 is that the amount of aluminate coupling agent is 30 g.
[0070] Example
[0071] Example 1
[0072] The dry surface resin is prepared by the following steps:
[0073] Step 1: Add 160g of polycarbonate diol, 13g of polyether diol, 55g of aliphatic isocyanate, 0.8g of chain extender, 0.5g of antioxidant, 3g of light stabilizer, and 0.05g of catalyst into a reactor, add 100g of mixed solvent, stir and mix, and react at 90°C for 3 hours to prepare a prepolymer;
[0074] Step 2: Add 400 g of mixed solvent to the prepolymer, cool to 50°C, add 25 g of diamine, and mix well to obtain a reaction solution;
[0075] Step 3: Add 235 g of mixed solvent, 0.4 g of terminator, 4 g of leveling agent, and 0.5 g of defoamer to the reaction solution, and mix well to obtain a dry surface layer resin with a solid content of 26.5%.
[0076] In this embodiment, the mixed solvent is prepared by mixing 575 g of N,N-dimethylformamide and 160 g of isopropanol.
[0077] In this embodiment, the model of the polycarbonate diol is 980R; the polyether diol is polytetramethylene glycol PTMEG-2000; the aliphatic isocyanate is 4,4'-dicyclohexylmethane diisocyanate; the chain extender is 1,4-butanediol; the model of the light stabilizer is LS-770 / TINUVIN292; the catalyst is the organic bismuth catalyst DY-20; the diamine is isophorone diamine; the terminator is methanol; the model of the leveling agent is BYK-333; and the model of the defoaming agent is BYK-A530.
[0078] In this embodiment, the antioxidant includes 0.25 g of hindered phenol antioxidant I-1010 and 0.25 g of phosphite antioxidant MIANOX168.
[0079] Example 2
[0080] The dry surface resin is prepared by the following steps:
[0081] Step 1: Add 165g of polycarbonate diol, 17g of polyether diol, 60g of aliphatic isocyanate, 1g of chain extender, 0.8g of antioxidant, 5g of light stabilizer, and 0.1g of catalyst into a reactor, add 150g of mixed solvent, stir and mix, and react at 90°C for 3 hours to prepare a prepolymer;
[0082] Step 2: add 500g of mixed solvent to the prepolymer, cool to 50°C, add 30g of diamine, and mix to obtain a reaction solution; Step 3: add 135g of mixed solvent, 0.5g of terminator, 5g of leveling agent and 1g of defoamer to the reaction solution, and mix to obtain a dry surface layer resin.
[0083] In this embodiment, the mixed solvent is prepared by mixing 600 g of N,N-dimethylformamide and 185 g of isopropanol.
[0084] Example 3
[0085] The dry surface resin is prepared by the following steps:
[0086] Step 1: Add 155g of polycarbonate diol, 9g of polyether diol, 50g of aliphatic isocyanate, 0.5g of chain extender, 0.2g of antioxidant, 2g of light stabilizer, and 0.02g of catalyst into a reactor, add 65g of mixed solvent, stir and mix, and react at 90°C for 3 hours to prepare a prepolymer;
[0087] Step 2: add 340g of mixed solvent to the prepolymer, cool to 50°C, add 20g of diamine, and mix to obtain a reaction solution; Step 3: add 280g of mixed solvent, 0.3g of terminator and 3g of leveling agent to the reaction solution, and mix to obtain a dry surface layer resin.
[0088] In this embodiment, the mixed solvent is prepared by mixing 550 g of N,N-dimethylformamide and 135 g of isopropanol.
[0089] Example 4
[0090] The only difference between this preparation example and Example 1 is that the aliphatic isocyanate is isophorone diisocyanate.
[0091] Example 5
[0092] The only difference between this example and Example 1 is that the aliphatic isocyanate includes 20 g of 4,4′-dicyclohexylmethane diisocyanate and 25 g of isophorone diisocyanate.
[0093] Example 6
[0094] The only difference between this embodiment and embodiment 1 is that the chain extender is ethylene glycol.
[0095] Example 7
[0096] The difference between this embodiment and embodiment 1 is only that:
[0097] Step 3 Add 235g of mixed solvent, 0.4g of terminator and 4g of leveling agent to the reaction solution, mix well to obtain the pre-set resin;
[0098] Step 4: Divide the pre-set resin into two parts, add 8g of filler to one part of the pre-set resin, and stir at 200r / min for 3h at 45℃; then add another part of the resin and 0.05g of defoaming agent, continue stirring for 2h and then cool to obtain a non-yellowing dry surface resin.
[0099] In this embodiment, the filler is ultrafine transparent powder with a particle size of 1250 mesh.
[0100] Example 8
[0101] The only difference between this embodiment and embodiment 7 is that the mass of the filler is 15 g.
[0102] Example 9
[0103] The only difference between this embodiment and embodiment 7 is that the filler is barium sulfate powder YF-6000.
[0104] Example 10
[0105] The only difference between this embodiment and embodiment 7 is that the filler is sericite powder with a particle size of 1250 mesh.
[0106] Embodiment 11
[0107] The only difference between this embodiment and embodiment 7 is that the filler is microcrystalline cellulose M105.
[0108] Example 12
[0109] The only difference between this embodiment and embodiment 7 is that the filler is 6.86 g of sericite powder and 1.14 g of microcrystalline cellulose.
[0110] Embodiment 13
[0111] The only difference between this embodiment and embodiment 7 is that the filler is 7 g of sericite powder and 1 g of microcrystalline cellulose.
[0112] Embodiment 14
[0113] The only difference between this embodiment and embodiment 7 is that the filler is 7.1 g of sericite powder and 0.9 g of microcrystalline cellulose.
[0114] Embodiment 15
[0115] The only difference between this embodiment and embodiment 7 is that the filler is the filler preparation example 1.
[0116] Example 16
[0117] The only difference between this embodiment and embodiment 7 is that the filler is the filler preparation example 2.
[0118] Embodiment 17
[0119] The difference between this embodiment and embodiment 7 is that the filler is the filler preparation example 3
[0120] Embodiment 18
[0121] The only difference between this embodiment and embodiment 1 is that the antioxidant includes 0.17 g of hindered phenol antioxidant and 0.33 g of phosphite antioxidant.
[0122] Embodiment 19
[0123] The only difference between this embodiment and embodiment 1 is that the antioxidant includes 0.125 g of hindered phenol antioxidant and 0.375 g of phosphite antioxidant.
[0124] Comparative Example
[0125] Comparative Example 1
[0126] The difference between this comparative example and Example 1 is that the aliphatic isocyanate is replaced by diphenylmethane diisocyanate among aromatic isocyanates.
[0127] Comparative Example 2
[0128] A method for preparing a dry surface layer resin comprises the following steps:
[0129] Step 1, weigh 102g polyester polyol, 103g polypropylene glycol, 0.01g poly (dipropylene glycol) phenyl phosphite antioxidant, 233g solvent and stir well, control the reaction temperature at 45°C;
[0130] Step 2, add 37.7g of diphenylmethane diisocyanate to step 1 and react for 1h, controlling the reaction temperature at 70°C;
[0131] Step 3, add 233g of solvent to step 2, make the temperature of the reaction system lower than 60°C, then add 1.4g of hexanediol chain extender, stir well for 0.5h, then add organic bismuth catalyst and continue the reaction for 0.5h, and control the reaction temperature at 70°C;
[0132] Step 4, add 30g of diphenylmethane diisocyanate to step 3 and continue the reaction for 1h, controlling the reaction temperature at 70°C;
[0133] Step 5, adding 234 g of acetone to dilute the viscosity of the reaction system, and then adding methanol to terminate the chain reaction;
[0134] Step 6: Finally, add 0.6 g of amino silicone oil, stir evenly, cool and discharge to obtain polyurethane resin.
[0135] Performance testing
[0136] The dry surface layer resin prepared in Example 1-19 and Comparative Example 1-2 was mixed with color paste and dimethylformamide at a weight ratio of 100:10:40, coated on release paper with a coating thickness of 0.3 mm, baked at 130° C. for 15 seconds, the release paper was aligned with the leather substrate, and then the release paper was peeled off and dried at 150° C.;
[0137] The veneered leather is softened, preheated at 130°C, heated at 200°C to soften, and then sent to a vacuum grain-absorbing machine. After grain-absorbing, it is cooled to obtain a leather sample.
[0138] The leather samples coated with the surface layers prepared in Examples 1-19 and Comparative Examples 1-2 were tested as follows:
[0139] Test 1: Yellowing resistance test: Cut the leather sample into 60mm*90mm test pieces, half of which are exposed and half are covered by a light shielding sheet, and put them into a UV resistance test box for testing. The UV light is 30W, the irradiation distance is 250mm, and the irradiation time is 48 / 72 hours. Refer to the standard GB / T250-1995 for color comparison;
[0140] Test 2: Color fastness test: Cut the leather sample into 220mm*60mm test pieces, refer to the standard GB / T3920-2008, and test it with a color fastness friction tester. The solvent is alcohol, the friction speed is 10 / 15 turns, and the color comparison is carried out according to the standard GB / T250-1995;
[0141] Test 3: Wear resistance test: refer to standard QB / T2726-200 for testing, and record the number of revolutions from friction to the end point;
[0142] The test results are shown in Table 1:
[0143] Table 1
[0144]
[0145] With reference to Table 1, in combination with Examples 1-6 and Comparative Examples 1-2, it can be seen that according to the method disclosed in the present application, aliphatic isocyanate is selected as a raw material, reacted with polycarbonate diol and polyether diol in the presence of a small molecule diol chain extender and a catalyst, and an antioxidant and a light stabilizer are added, which can effectively improve the light stability and yellowing resistance of the dry surface resin.
[0146] Combining Example 1 and Comparative Example 1, it can be seen that aliphatic isocyanate can reduce the wear resistance of dry surface resin compared with aromatic isocyanate. Combining Examples 6 and 7, adding fillers to dry surface resin can significantly improve the wear resistance and alcohol color fastness of the resin, giving the dry surface resin better performance.
[0147] In combination with Example 1, Example 7, and Examples 9-11, it is shown that when sericite powder and microcrystalline cellulose are respectively selected as fillers, the wear resistance and alcohol color fastness of the dry surface resin can be improved while the light stability and yellowing resistance can be enhanced; the sericite powder can effectively shield ultraviolet rays and block water molecules from penetrating into the dry surface resin, reducing the possibility of hydrolysis and photo-oxidation of polyurethane molecules; the microcrystalline cellulose can be dispersed in the dry surface resin to effectively absorb the infiltrated water molecules and delay the hydrolysis of the polyurethane molecules.
[0148] Combined with Examples 10-11 and 12-13, it is shown that when sericite powder and microcrystalline cellulose are selected as fillers at the same time, the two can play a synergistic role. The sericite powder can form a densely stacked sericite layer, which can effectively shield ultraviolet rays and block water molecules. The microcrystalline cellulose dispersed between the layers can absorb water molecules that penetrate through the sericite layer, further reducing the possibility of polyurethane molecules being hydrolyzed. At the same time, the microcrystalline cellulose can stabilize the sericite layer. The two can work together to effectively improve the yellowing resistance of the dry surface resin.
[0149] In combination with Example 12 and Examples 15-17, it can be seen that the use of an aluminate coupling agent to treat the filler surface can further enhance the mechanical properties of the dry surface resin, such as wear resistance, and facilitate the dispersion of the filler in the dry surface resin.
[0150] Combining Example 1 with Examples 18-19, it is shown that the use of hindered phenol antioxidants and phosphite antioxidants can effectively slow down the rate of photooxidation and enhance the yellowing resistance of the dry surface resin.
[0151] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A non-yellowing dry surface resin, characterized in that: The composition comprises the following components in parts by weight: 155-165 parts of polycarbonate diol, 9-17 parts of polyether diol, Aliphatic isocyanate 50-60 parts, 20-30 parts of diamine, Chain extender 0.5-1 part, Antioxidant 0.2-0.8 parts, Catalyst 0.02-0.1 parts, Terminator 0.3-0.5 parts, 3-5 parts of leveling agent, Light stabilizer 2-5 parts, 685-785 parts of solvent, 15 parts of filler, Defoaming agent 0-0.1 part; The filler comprises sericite powder and microcrystalline cellulose in a mass ratio of 6-8:
1.
2. The non-yellowing dry-process surface layer resin according to claim 1, characterized in that: The aliphatic isocyanate is selected from one or a combination of 4,4'-dicyclohexylmethane diisocyanate and isophorone diisocyanate.
3. The non-yellowing dry-process surface resin according to claim 1, characterized in that: The diamine is isophoronediamine.
4. The non-yellowing dry-process surface resin according to claim 1, characterized in that: The chain extender is selected from one or a combination of ethylene glycol, propylene glycol or 1,4-butanediol.
5. The non-yellowing dry-process surface resin according to claim 1, characterized in that: The filler is a surface-treated filler, and the specific operation is as follows: s1 Bake the filler at 100°C-130°C for 2-4h, and stir and mix at 65°C-70°C and 500-700r / min; s2 melt the aluminate coupling agent at 70°C-75°C; s3: Mix the filler with a mass ratio of 100:1-3 and the melted aluminate coupling agent at 80°C-90°C, stir at a speed of 300-500 r / min for 20-30 minutes, and then cool at room temperature to obtain a surface-treated filler.
6. The non-yellowing dry-process surface resin according to claim 1, characterized in that: The antioxidant comprises a hindered phenol antioxidant and a phosphite antioxidant in a mass ratio of 1:1-3.
7. The non-yellowing dry-process surface resin according to claim 1, characterized in that: The solvent comprises 135-185 parts of isopropanol and 550-600 parts of N,N-dimethylformamide per part by weight.
Citation Information
Patent Citations
Alcohol-solvent-resistant, wear-resistant and yellowing-resistant surface polyurethane resin and preparation method thereof
CN106317366A
Hydrolysis-resistant PU synthetic leather and production method thereof
CN111519444A
Anti-aging and algae-resistant PVC composition for outdoor colored lamps and preparation method of anti-aging and algae-resistant PVC composition
CN113754970A